Peptides-Based Vaccine MP3RT Induced Protective Immunity Against Mycobacterium Tuberculosis Infection in a Humanized Mouse Model - Gong, Wenping; Liang, Yan; Mi, Jie; Jia, Zaixing; Xue, Yong; Wang, Jie; Wang, Lan; Zhou, Yusen; Sun, Shihui; Wu, Xueqiong (Frontiers in Immunology, 2021)
Background Tuberculosis (TB) is still a global infectious disease that seriously threatens human beings. The only licensed TB vaccine Bacille Calmette-Guérin (BCG)’s protective efficacy varies significantly among populations and regions. It is very urgent to develop more effective vaccines. Methods In this study, eleven candidate proteins of Mycobacterium tuberculosis were selected to predict peptides with high-affinity binding capacity for the HLA-DRB1*01:01 molecule. The immunodominant peptides were identified with the enzyme-linked immunospot assay (ELISPOT) and linked in silico to result in a novel polypeptide vaccine in Escherichia coli cells. The vaccine’s protective efficacy was evaluated in humanized and wild-type C57BL/6 mice. The potential immune protective mechanisms were explored with Enzyme-linked Immunosorbent Assay (ELISA), flow cytometry, and ELISPOT. Results Six immunodominant peptides screened from 50 predicted peptides were used to construct a new polypeptide vaccine named MP3RT. After challenge with M. tuberculosis, the colony-forming units (CFUs), lung lesion area, and the number of inflammatory cells in humanized mice rather than wild-type mice vaccinated with MP3RT were significantly lower than these in mice immunized with PBS. The humanized mice vaccinated with MP3RT revealed significant increases in IFN-γ cytokine production, IFN-γ+ T lymphocytes, CD3+IFN-γ+ T lymphocytes, and the MP3RT-specific IgG antibody. Conclusions Taken together, MP3RT is a promising peptides-based TB vaccine characterized by inducing high levels of IFN-γ and CD3+IFN-γ+ T lymphocytes in humanized mice. These new findings will lay a foundation for the development of peptides-based vaccines against TB.